1988
DOI: 10.1002/pssa.2211090213
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of amorphous thin films of MoO3 deposited by vacuum evaporation

Abstract: The absorption spectra of MoO3 amorphous thin films in the thickness range from 50 to 350 nm are studied as a function of thickness in the temperature range from 20 to 275°C. The validity of the Urbach rule is investigated and the related parameters are estimated. It is confirmed that absorption in these layers is due to non‐direct transitions. A decrease in optical energy gap with annealing is reported. The analysis of optical absorption edge as a function of temperature is discussed with particular reference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
28
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(35 citation statements)
references
References 20 publications
7
28
0
Order By: Relevance
“…The structure of the films and the physical properties have shown to be markedly dependent on the substrate temperature. Anwar et al [6] and Muranaka [11] have suggested that the films of MoO3 and In203 prepared on substrates at a temperature of 270°C or higher are crystalline in character, but the present investigation showed that the mixed MoO3-In203 complex oxide films are amorphous in character at 270 ° C substrate temperature. Anwar et al [16] have studied MoO3 films at higher substrate temperatures and reported the formation of molybdenum species of lower oxidation state (i.e.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…The structure of the films and the physical properties have shown to be markedly dependent on the substrate temperature. Anwar et al [6] and Muranaka [11] have suggested that the films of MoO3 and In203 prepared on substrates at a temperature of 270°C or higher are crystalline in character, but the present investigation showed that the mixed MoO3-In203 complex oxide films are amorphous in character at 270 ° C substrate temperature. Anwar et al [16] have studied MoO3 films at higher substrate temperatures and reported the formation of molybdenum species of lower oxidation state (i.e.…”
Section: Discussionmentioning
confidence: 76%
“…Molybdenum boats were used for the evaporation of both MoO3 and In203. All other techniques used to measure film thickness, cleaning of the substrates, raising the substrate temperature, absorption measurements, transmission electron microscopy and annealing the samples in vacuum are the same as described earlier by Anwar and Hogarth [6].…”
Section: Experimental Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…• The loss of transmittance or increase in absorptance in some of the annealed-thin films, over the photon energy range from 0.4 eV to 3.0 eV, is attributed not only to slight grain growth but also to the development of rough surfaces on the top layers of these samples. 46 • The Mo 5+ ions in the Mo 6+ oxide lattice are still responsible for the strong absorption band in the red part of the spectrum.The values of the thermal-activation energy of the reported data have been gauged in the range 0.37-0.41 eV, 22 which, in fact, still cover the semiconducting range. The opticalactivation energy has also been found to be of about 1.5-1.65 eV for the investigated annealed samples, and this is a characteristic signal of intervalence transfer or a polaronic type of absorption.…”
Section: Coloration Bands and Polaronic Modelmentioning
confidence: 99%
“…higher electronic conductivities of the molybdenum oxide did result in an improved battery performance. The colour of the sub-stoichiometric MOO3_ x compounds varied from light blue to dark blue [14]. At contrast, the colour of stoichiometric M o O 3 is pure white to light yellow, indicating a low electronic conductivity.…”
Section: Introductionmentioning
confidence: 97%